Antibody Therapy of Pediatric B-Cell Lymphoma - Meyer-Wentrup, Friederike; de Zwart, Verena; Bierings, Marc (Frontiers in Oncology, 2013)
B-cell lymphoma in children accounts for about 10% of all pediatric malignancies. Chemotherapy has been very successful leading to an over-all 5-year survival between 80 and 90% depending on lymphoma type and extent of disease. Therapeutic toxicity remains high calling for better targeted and thus less toxic therapies. Therapeutic antibodies have become a standard element of B-cell lymphoma therapy in adults. Clinical experience in pediatric lymphoma patients is still very limited. This review outlines the rationale for antibody treatment of B-cell lymphomas in children and describes potential target structures on B-cell lymphoma cells. It summarizes the clinical experience of antibody therapy of B-cell lymphoma in children and gives an outlook on new developments and challenges for antibody therapy of pediatric B-cell lymphoma.